EFEKTIVITAS METODE HUKUMAN BERBASIS NILAI-NILAI ISLAM DI SMPIT AR-RAHMAH PACITAN: SEBUAH PENDEKATAN INOVATIF - Hamdani, Mohammad Khusnul (LPPM STAI Muhammadiyah Probolinggo, 2022)
This study aims to determine the effectiveness of the Islamic values-based punishment method applied at SMPIT Ar-Rahmah Pacitan as an innovative approach in disciplining students. The background of this study is based on the need for a punishment method that not only avoids the negative impacts of physical punishment, but also contributes to the formation of students' character in accordance with Islamic teachings. The research method used is a qualitative approach with observation, interviews, and documentation analysis to collect data from teachers, students, and schools. The results of the study indicate that the Islamic values-based punishment method, such as training through advice, memorizing verses of the Qur'an, and reflective tasks, is effective in improving students' discipline and spiritual awareness. This punishment not only reduces negative behavior, but also encourages students' cognitive and emotional development. In addition, this approach strengthens the relationship between teachers and students, creating a more positive and supportive learning environment. In conclusion, the Islamic values-based punishment method can be an effective innovative alternative in improving student discipline and character formation at SMPIT Ar-Rahmah Pacitan. Keywords: Innovation; Punishment; Islamic Education.